2015
DOI: 10.1590/s1519-99402015000200020
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do dispositivo intravaginal de progesterona, em até três usos, para inseminação artificial em tempo fixo de fêmeas Bos indicus

Abstract: Objetivou-se avaliar o efeito do número de utilizações (até três) do CIDRÒ, manifestação de estro e ordem de parição sobre a taxa de prenhez em vacas Bos indicus. Utilizou-se 1176 vacas pluríparas e primíparas, lactantes, 30 a 60 dias pós-parto. Os grupos receberam CIDRÒ de primeiro, segundo ou terceiro usos, mais 2,0 mg de benzoato de estradiol no dia de introdução (D0) e, 500 μg de dinoprost trometamina, 300 UI de eCG e 0,6 mg de cipionato de estradiol na retirada dos dispositivos (D8), com a IATF 48 horas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the present study, we found similar P/AI in the two groups (56.2% for GRN and 57.0% for GRU; p > 0.05), because both groups were subjected to the same hormonal protocol (Table ). While working with Bos taurus indicus cows, Medalha et al () obtained significantly lower P/AI values (44.8%) using new intravaginal devices with P4. Therefore, significant variations in the P/AI of cows subjected to the TAI protocol were found in several studies, and these variations have persisted over time, with few exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found similar P/AI in the two groups (56.2% for GRN and 57.0% for GRU; p > 0.05), because both groups were subjected to the same hormonal protocol (Table ). While working with Bos taurus indicus cows, Medalha et al () obtained significantly lower P/AI values (44.8%) using new intravaginal devices with P4. Therefore, significant variations in the P/AI of cows subjected to the TAI protocol were found in several studies, and these variations have persisted over time, with few exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…There is no effect of intravaginal progesterone implant of up to third use on the pregnancy rate of heifers 2 and 3), demonstrating that intravaginal progesterone(P4) devices can be reused, allowing the start of the synchronization of the cycle from lower concentrations of this hormone, without reducing conception rates, being a viable and efficient way to perform the TAI Medalha et al, 2015). The results of this work corroborate those published in the literature on the reuse of heifer progesterone device implants up to 3 times (Carvalho et al, 2019;Medalha et al, 2015;Gottschall et al, 2012).…”
Section: Variable Odds Ration P Valuementioning
confidence: 99%
“…There is no effect of intravaginal progesterone implant of up to third use on the pregnancy rate of heifers 2 and 3), demonstrating that intravaginal progesterone(P4) devices can be reused, allowing the start of the synchronization of the cycle from lower concentrations of this hormone, without reducing conception rates, being a viable and efficient way to perform the TAI Medalha et al, 2015). The results of this work corroborate those published in the literature on the reuse of heifer progesterone device implants up to 3 times (Carvalho et al, 2019;Medalha et al, 2015;Gottschall et al, 2012). The use of fourth-use intravaginal progesterone devices is an effective alternative for inducing puberty in heifers, thus, the authors reported a pregnancy rate of 35.14% in this category (Coelho et al (2021), and in the same In this sense, Figueredo et al, (2019) found a pregnancy rate of 48.18% also in beef heifers and under conditions similar to those observed in this study.…”
Section: Variable Odds Ration P Valuementioning
confidence: 99%
See 2 more Smart Citations